2019
DOI: 10.1002/advs.201901555
|View full text |Cite
|
Sign up to set email alerts
|

An “Amyloid‐β Cleaner” for the Treatment of Alzheimer's Disease by Normalizing Microglial Dysfunction

Abstract: Alzheimer's disease (AD) is a devastating neurodegenerative disorder characterized by progressive cognitive and memory loss. The vicious circle between dysfunctional microglia and amyloid‐β (Aβ) is a crucial pathological event and accelerates the progression of AD. Herein, a zwitterionic poly(carboxybetaine) (PCB)‐based nanoparticle (MCPZFS NP) with normalizing the dysfunctional microglia and Aβ recruitment is established for the treatment of AD. Compared with the neural polyethylene glycol (PEG)‐based nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 53 publications
0
64
0
Order By: Relevance
“…The mice were placed individually in the pool facing the pool wall. The ratio of the time in the original quadrant of the total time was recorded, and the number of times that the rat crossed the original platform in 90 s was measured [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mice were placed individually in the pool facing the pool wall. The ratio of the time in the original quadrant of the total time was recorded, and the number of times that the rat crossed the original platform in 90 s was measured [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nanoparticle-based AD treatment has been explored recently in the literature. Liu et al reported on AD treatment application by zwitterionic poly(carboxybetaine) (PCB)-based nanoparticles coloaded with fingolimod, siSTAT3, and zinc oxide, henceforth named MCPZFS nanoparticles or MCPZFS NPs [ 185 ]. The diameter of the MCPZF NPs was between 84.0 and 89.4 nm.…”
Section: Nanomedicine-based Immunotherapy For Neurodegenerative Disormentioning
confidence: 99%
“…The diameter of the MCPZF NPs was between 84.0 and 89.4 nm. A mannose analog 4-aminophenyl α-d-mannopyranoside (Man) was added to the nanoparticles to facilitate BBB penetration and improve the targeting of microglia [ 185 ]. MCPZFS nanoparticles significantly improve microglial priming by reducing the level of proinflammatory mediators and promoting the secretion of brain-derived neurotrophic factor (Fig.…”
Section: Nanomedicine-based Immunotherapy For Neurodegenerative Disormentioning
confidence: 99%
See 2 more Smart Citations